Perancangan dan Pembuatan Website E-Commerce Penjualan Spare part UD. Cahaya Agung Motor - Cindy Chandiarie; Silvia Rostianingsih; Djoni Haryadi Setiabudi (Jurnal Infra, 2018)
UD. Cahaya Agung Motor located in Makassar, South Sulawesi has problems with customers who are outside the city, they have to come to UD to buy the goods they want or order goods by phone or SMS. If UD is busy buyer, owner or employee will be difficult to pick up phone or serve SMS customer, consequently customer will be neglected and switch to another store to buy goods. To overcome the existing problems then created an e-commerce-based website that allows customers to buy the desired goods without having to come to UD to buy.The design of this website is designed using Data Flow Diagrams (DFD), Entity Relationship Diagram (ERD) using programming languages PHP and HTML and MySQL as database software. In this website there are various information needed by the customer, such as to know the brand, image and spare part price so that customers can know more clearly the spare part to be purchased. For payment, customers can also choose the type of payment provided such as credit card, transfer and joint account. This website also has master data information such as sales list, master customer, master return and master goods on the admin page and data reports such as sales reports, stock items and return reports that can be viewed by the owner.The result of the design of the application created is an e-commerce website that can assist customers in making purchases 24 hours and can be reached throughout Indonesia. The conclusions obtained from testing the website conducted by the customer and admin is that this website is running well in accordance with the wishes of the user and this website helps in improving work efficiency for UD owners and provide information fast and user friendly.